SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN PAI SD IPK HIDAYAH TAYU - Nor Faizah; Habibul Luthfi; Moh Sholihudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the principal’s supervisory strategies in improving the quality of Islamic Religious Education (PAI) learning at SD IPK Hidayah Tayu. Using a qualitative approach, data were collected through interviews, observations, and document analysis, with the principal as the primary research subject. The findings indicate that improving the quality of PAI learning is carried out through six main strategies: (1) internal enhancement through socialization of teachers’ roles and responsibilities; (2) academic supervision through classroom visits and lesson plan (RPP) evaluation; (3) evaluation of teaching and learning activities (KBM) to identify obstacles and provide constructive feedback to teachers; (4) fostering teacher discipline to strengthen professionalism; (5) school promotion to increase student participation; and (6) improvement of facilities and infrastructure to support the learning process. These findings demonstrate that the principal's supervision plays a significant role in creating an effective and high-quality learning environment, particularly in enhancing the quality of PAI learning.